Development of a Flow Cytometry Assay to Predict Immune Checkpoint Blockade-Related Complications - Schilling, Hannah-Lou; Glehr, Gunther; Kapinsky, Michael; Ahrens, Norbert; Riquelme, Paloma; Cordero, Laura; Bitterer, Florian; Schlitt, Hans J.; Geissler, Edward K.; Haferkamp, Sebastian; Hutchinson, James A.; Kronenberg, Katharina (Frontiers in Immunology, 2021)
Treatment of advanced melanoma with combined immune checkpoint inhibitor (ICI) therapy is complicated in up to 50 % of cases by immune-related adverse events (irAE) that commonly include hepatitis, colitis and skin reactions. We previously reported that pre-therapy expansion of cytomegalovirus (CMV)-reactive CD4+ effector memory T cells (TEM) predicts ICI-related hepatitis in a subset of patients with Stage IV melanoma given αPD-1 and αCTLA-4. Here, we develop and validate a 10-color flow cytometry panel for reliably quantifying CD4+ TEM cells and other biomarkers of irAE risk in peripheral blood samples. Compared to previous methods, our new panel performs equally well in measuring CD4+ TEM cells (agreement = 98 %) and is superior in resolving CD4+ CD197+ CD45RA- central memory T cells (TCM) from CD4+ CD197+ CD45RA+ naive T cells (Tnaive). It also enables us to precisely quantify CD14+ monocytes (CV = 6.6 %). Our new “monocyte and T cell” (MoT) assay predicts immune-related hepatitis with a positive predictive value (PPV) of 83 % and negative predictive value (NPV) of 80 %. Our essential improvements open the possibility of sharing our predictive methods with other clinical centers. Furthermore, condensing measurements of monocyte and memory T cell subsets into a single assay simplifies our workflows and facilitates computational analyses.